2008
DOI: 10.1038/nature06475
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial enzyme RppH triggers messenger RNA degradation by 5′ pyrophosphate removal

Abstract: The long-standing assumption that messenger RNA (mRNA) degradation in Escherichia coli begins with endonucleolytic cleavage has been challenged by the recent discovery that RNA decay can be triggered by a prior non-nucleolytic event that marks transcripts for rapid turnover: the rate-determining conversion of the 5' terminus from a triphosphate to a monophosphate. This modification creates better substrates for the endonuclease RNase E, whose cleavage activity at internal sites is greatly enhanced when the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
454
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(469 citation statements)
references
References 30 publications
14
454
0
1
Order By: Relevance
“…Previous studies have shown that mRNA degradation by a 5′-end-dependent pathway requires a single-stranded 5′ terminus in both B. subtilis and E. coli (7,10). However, the number of unpaired 5′-terminal nucleotides required for degradation by this mechanism had not been determined in these or any other species.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown that mRNA degradation by a 5′-end-dependent pathway requires a single-stranded 5′ terminus in both B. subtilis and E. coli (7,10). However, the number of unpaired 5′-terminal nucleotides required for degradation by this mechanism had not been determined in these or any other species.…”
Section: Discussionmentioning
confidence: 89%
“…However, we have recently described an alternative degradation pathway in B. subtilis in which the decay of primary transcripts is triggered by the RNA pyrophosphohydrolase RppH (previously known as YtkD), a Nudix hydrolase that removes two of the three 5′-terminal phosphates to generate a full-length intermediate that is monophosphorylated and therefore vulnerable to rapid 5′-exonucleolytic digestion by RNase J (7). A related 5′-end-dependent pathway is also present in bacterial species that lack RNase J, such as E. coli, where pyrophosphate removal triggers rapid cleavage by RNase E, the endonucleolytic activity of which is stimulated by a 5′ monophosphate (8)(9)(10).…”
mentioning
confidence: 99%
“…It has been known for some time that strong secondary structures, bound proteins and, in particular, strong ribosome binding sites the simplest explanation is that the generation of the shorter, stable ∆ermC and lac-rpsO transcripts, like those of cryIIIA and hbs, is dependent on RNase J1 5'-3' exoribonuclease activity, with an entry site provided by another enzyme, either removal of the 5' tri-phosphate group by an enzyme equivalent to the E. coli RNA pyrophosphohydrolase RppH, 24 or an endonucleolytic cleavage downstream of the 5' end (Fig. 1).…”
Section: Role Of Rnase J1/j2 In the Turnover Of Specific Rnasmentioning
confidence: 99%
“…In this report, we present a previously undescribed mechanism for the sequence-specific binding of single-stranded RNA by the 25 kDa subunit of CFI m . Although the Nudix domains of the eukaryotic decapping enzymes (18), bacterial 5′ pyrophophohydrolase (19), and the trypanosome mitochondrial protein MERS1 (20) act on RNA, CFI m 25 is unique among Nudix proteins in that it is capable of sequencespecific RNA binding. CFI m 25 is highly conserved throughout the eukaryotic kingdom (Fig.…”
mentioning
confidence: 99%